Irisin Preserves Cardiac Performance and Insulin Sensitivity in Response to Hemorrhage - Supaporn Kulthinee; Lijiang Wang; Naohiro Yano; Patrycja M. Dubielecka; Ling X. Zhang; Shougang Zhuang; Gangjian Qin; Yu Tina Zhao; Yue Eugene Chin; Ting C. Zhao (MDPI AG, 2022)
Irisin, a cleaved product of the fibronectin type III domain containing protein-5, is produced in the muscle tissue, which plays an important role in modulating insulin resistance. However, it remains unknown if irisin provides a protective effect against the detrimental outcomes of hemorrhage. Hemorrhages were simulated in male CD-1 mice to achieve a mean arterial blood pressure of 35-45 mmHg, followed by resuscitation. Irisin (50 ng/kg) and the vehicle (saline) were administrated at the start of resuscitation. Cardiac function was assessed by echocardiography, and hemodynamics were measured through femoral artery catheterization. A glucose tolerance test was used to evaluate insulin sensitivity. An enzyme-linked immunosorbent assay was performed to detect inflammatory factors in the muscles and blood serum. Western blot was carried out to assess the irisin production in skeletal muscles. Histological analyses were used to determine tissue damage and active-caspase 3 apoptotic signals. The hemorrhage suppressed cardiac performance, as indicated by a reduced ejection fraction and fractional shortening, which was accompanied by enhanced insulin resistance and hyperinsulinemia. Furthermore, the hemorrhage resulted in a marked decrease in irisin and an increase in the production of tumor necrosis factor-α (TNF-α) and interleukin-1 (IL-1). Additionally, the hemorrhage caused marked edema, inflammatory cell infiltration and active-caspase 3 positive signals in skeletal muscles and cardiac muscles. Irisin treatment led to a significant improvement in the cardiac function of animals exposed to a hemorrhage. In addition, irisin treatment improved insulin sensitivity, which is consistent with the suppressed inflammatory cytokine secretion elicited by hemorrhages. Furthermore, hemorrhage-induced tissue edema, inflammatory cell infiltration, and active-caspase 3 positive signaling were attenuated by irisin treatment. The results suggest that irisin protects against damage from a hemorrhage through the modulation of insulin sensitivity.